Triggering thresholds and influential factors in the propagation of meteorological drought to hydrological drought - Na Zhen; Rui Yao; Peng Sun; Qiang Zhang; Chenhao Ge; Han Shen (Journal of Hydrology: Regional Studies)
Study regions: The Huaihe River Basin (HRB), China Study focus: Quantifying the thresholds for the systematic propagation of meteorological drought (MD) to different levels of hydrological drought (HD) is essential for early warning and precision management of HDs. This study employs the non-stationary Normalized Standardized Precipitation Evapotranspiration Index (NSPEI) and the Standardized Runoff Index (SRI) from 1980 to 2019 to delineate MD and HD. Using Copula functions and Bayesian networks, it jointly analyzes the evolutionary characteristics of MDs and HDs in different sub-basins of the HRB, quantitatively investigates the thresholds for the propagation of MD to HD, and identifies potential influencing factors on these thresholds. New hydrological insights for the region: The study identifies 1991 as a change point, indicating that: After 1991, the thresholds for drought propagation exceeded their pre-1991 values, with mean thresholds increasing by 3.1 for drought duration and 2.8 for drought severity. The probability of drought propagation significantly decreased after 1991, declining from 62.34 % to 48.69 %. Bantai Station is primarily influenced by climate change, resulting in an increase in the drought duration propagation threshold from 12.2 to 17.5. Under similar climatic conditions, human impact at Wangjiaba Station is more pronounced than at Xixian Station. Hence, the transmission probability at Wangjiaba Station decreases significantly, while the transmission duration threshold rises from 11.6 to 13.5.